2014
DOI: 10.1016/j.breast.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The Central-European SentiMag study: Sentinel lymph node biopsy with superparamagnetic iron oxide (SPIO) vs. radioisotope

Abstract: Sentinel lymph node biopsy (SLNB) is the standard surgical procedure for the axilla in early node-negative breast cancer. To date, the "gold standard" to localize the sentinel lymph node (SLN) is the radiotracer (99m)Tc with or without blue dye. The aim of this study was to evaluate potential equivalency of the new SentiMag(®) technique in comparison to the "gold standard". Within this prospective, multicentric and multinational non-inferiority study including 150 patients (99m)Tc was compared with the magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
159
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 23 publications
8
159
1
9
Order By: Relevance
“…Shiozawa et al [16] (would be good here to list how many patients, and maybe give this trial a name to -to be consistent with he other two) reported a false negative rate of 17 per cent using the magnetic technique and even the SentiMAG Multicentre Trial, [17] which was found to be non-inferior to the dual technique for SLN identification demonstrated a false negative rate of 8 per cent and 4 per cent for the magnetic and dual techniques respectively. The Central-European SentiMag Study [18] identified a lower false negative rate for the magnetic technique of 3 per cent versus 9 per cent for the standard radioisotope technique, inconsistent with the previous studies. The higher false negative rate in the standard technique in this trial may be explained by the omission of blue dye, which is known to improve the SLN identification rate and lower the false negative rate of the dual technique.…”
Section: Introductioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Shiozawa et al [16] (would be good here to list how many patients, and maybe give this trial a name to -to be consistent with he other two) reported a false negative rate of 17 per cent using the magnetic technique and even the SentiMAG Multicentre Trial, [17] which was found to be non-inferior to the dual technique for SLN identification demonstrated a false negative rate of 8 per cent and 4 per cent for the magnetic and dual techniques respectively. The Central-European SentiMag Study [18] identified a lower false negative rate for the magnetic technique of 3 per cent versus 9 per cent for the standard radioisotope technique, inconsistent with the previous studies. The higher false negative rate in the standard technique in this trial may be explained by the omission of blue dye, which is known to improve the SLN identification rate and lower the false negative rate of the dual technique.…”
Section: Introductioncontrasting
confidence: 70%
“…This means that the control of the performance of SLNB is directly within the hands of the operating surgeon who administers the magnetic tracer. All 3 published clinical studies [16][17][18] for the use of the magnetic technique injected the magnetic tracers after induction of general anaesthetic, periareolarly into the breast. Although the optimal timing of the magnetic tracer is not yet known, our results suggest that a pre-operative injection (4 hours or more prior to surgery) is likely to significantly improve the percutaneous magnetometer count and by doing so, improve the identification rate.…”
Section: ]mentioning
confidence: 99%
See 3 more Smart Citations